Physicochemical changes and emissions impact during co-composting of grease trap solid waste and rice husk - Lee, L. X.; Haslan, H. A.; Tan, P. Q.; Mohamed Fauzi, N. F.E.; Roslan, A. M.; Ariffin, H.; Mohd Yusoff, M. Z.; Ramli, N.; Abdul-Mutalib, N. A. (Springer Nature, 2025)
Despite the challenges encountered in grease trap solid waste (GTSW) composting reported in previous studies, a new composting strategy to utilise GTSW effectively was not developed yet. Therefore, this study proposed co-composting GTSW with rice husk and aimed to investigate the physicochemical properties changes, gaseous emission and biocompost quality of GTSW-rice husk co-composting. The process was conducted in 120 L in-vessel composting reactor at 30:1 initial C/N ratio, 60% (v/w) initial moisture content and turning frequency of one to three times a week. Results showed that GTSW-rice husk co-composting reached maturity in 70 days. During thermophilic phase, a temperature of 40–50 °C was sustained for 46–47 days, oxygen level was relatively low but maintained above zero, and methane was found below the detection limit. Active composting led moisture content and C/N ratio decreased from 60 and 63% to 47–53% (v/w) and 30:1–32:1 to 21:1–23:1, whereas pH and EC increased from 4.9–5.9 to 7.8–8.0 and 292–400 μS/cm to 1050–1240 μS/cm, attributing to microbial decomposition of organic matter. A significant positive association (p < 0.01) was found between moisture and carbon, moisture and C/N ratio, pH and EC, carbon and C/N ratio. The final biocompost produced complied with U.S. EPA compost standard, being nutritious and non-phytotoxic. However, phosphorus and potassium contents of biocompost needed enhancement before application. This study could serve as a basis to reshape GTSW management into a sustainable operation.